Hrestomatija medicinskega prava (University of Maribor Press, 2020)
Chrestomathy of Medical Law. The publication focuses on selected issues of medical law that relate in many ways to the patient’s rights, duties and responsibilities. The patient is no longer a passive actor, but has turned into an active actor when decisions are made about his/her health and even his/her life. However, as law and medicine are very dynamic fields, understanding of patients’ rights in recent years has undergone rapid development and related legislative changes in Slovenia and Croatia, as well as at EU and international level. The case law has also been enriched, which has also a crucial influence on the development and on the contemporary approach to the understanding of patients’ rights. The publication offers a broad approch to handling of current legal questions related to medical law (eg. GDPR, right to privacy, criminal liability, ....), as well as the issues raised by medicine, law and, last but not least, (bio)ethics regarding patients’ rights, duties and responsibilities on the one hand, as well as the competencies and responsibilities of healthcare professionals, healthcare organizations and health systems on the other hand.